The role of cathepsin S in the pathophysiology of bronchial asthma - A. Yu. Kraposhina; E. А. Sobko; I. V. Demko; O. V. Kazmerchuk; A. B. Kacer; Yu. I. Abramov (Бюллетень сибирской медицины)
To date, the study of the role of proteases in the pathogenesis of various diseases remains relevant. The variety of cathepsin functions is associated with the peculiarities of their localization, expression, and regulation, due to which cathepsins are involved in development of many pathologies. Dysregulation of proteases, their inhibitors, and substrates can lead to the development of multiple organ dysfunction.The review presents data on the characteristics of the entire family of cathepsins and cathepsin S, in particular. The pathophysiological role of cathepsin S in the formation of bronchopulmonary pathologies, as well as in bronchial asthma is described, and intraand extracellular implementation mechanisms are considered. The authors believe it is this enzyme that could be targeted in targeted asthma therapy to prevent airway wall remodeling at the earliest stages of the disease. The literature search was carried out in the search engines Medline, eLibrary, Scopus, the Cochrane Library, and RSCI.